2018
DOI: 10.1021/acs.jpcc.7b11110
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic Stability of Molybdenum Oxycarbides Formed from Orthorhombic Mo2C in Oxygen-Rich Environments

Abstract: Molybdenum carbide (Mo2C) nanoparticles and thin films are particularly suitable catalysts for catalytic fast pyrolysis (CFP) as they are effective for deoxygenation and can catalyze certain reactions that typically occur on noble metals. Oxygen deposited during deoxygenation reactions may alter the carbide structure leading to the formation of oxycarbides, which can determine changes in catalytic activity or selectivity. Despite emerging spectroscopic evidence of bulk oxycarbides, so far there have been no re… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(20 citation statements)
references
References 83 publications
3
16
0
Order By: Relevance
“…The five MoC phases are δ-MoC, , α-MoC, , G-MoC, η-MoC, ,, and TiP-MoC , ­(it is denoted γ′ in refs and ), as shown in Figure c–g, respectively. The two Mo 2 C phases are β-Mo 2 C ,, and α-Mo 2 C, ,, as shown in Figure a,b, respectively. The structural parameters of different Mo x C ( x = 1, 2) phases, including space group, number of formula units, lattice parameters, cohesive energy, as well as theoretical and experimental data from previous literature, are listed in Table S1.…”
Section: Resultsmentioning
confidence: 93%
“…The five MoC phases are δ-MoC, , α-MoC, , G-MoC, η-MoC, ,, and TiP-MoC , ­(it is denoted γ′ in refs and ), as shown in Figure c–g, respectively. The two Mo 2 C phases are β-Mo 2 C ,, and α-Mo 2 C, ,, as shown in Figure a,b, respectively. The structural parameters of different Mo x C ( x = 1, 2) phases, including space group, number of formula units, lattice parameters, cohesive energy, as well as theoretical and experimental data from previous literature, are listed in Table S1.…”
Section: Resultsmentioning
confidence: 93%
“…Postreaction characterization with XPS showed that O adatoms were always the dominant species on this surface with a very small amount (<0.05 ML) of a carbonate. The hydrogen atoms generated by H 2 dissociation on this system are not reactive enough to remove the O adatoms yielded by CO 2 decomposition, the catalyst is metastable, and the carbide NPs transform into a highly stable oxycarbide which also has been detected on surfaces and powders of bulk Mo 2 C. 14,16,36,37 The product distribution seen for the hydrogenation of CO 2 on MoC 0.6 /Au(111) is similar to that reported for NPs of Mo 2 C which are mainly methanation or Fischer−Tropsch catalysts. 13 On the other hand, Figure 3 summarizes the results for the hydrogenation of CO 2 on MoC 1.1 /Au(111).…”
Section: ■ Results and Discussionmentioning
confidence: 98%
“…3 ). The stability of the orthorhombic Mo 2 C and Mo 2 CO x phases has been previously evaluated by DFT calculations 48 , 49 . We derived 2D-Mo 2 C surface from the crystal structure of Mo 2 Ga 2 C, slicing it along the 001 direction, since it is the most convenient approach to obtain a 2D system with the desired stoichiometry (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%